2008
DOI: 10.1055/s-2008-1039717
|View full text |Cite
|
Sign up to set email alerts
|

Extrakorporale Stoßwellentherapie bei der Tendionosis calcarea der Rotatorenmanschette: Vergleich verschiedener Behandlungsprotokolle

Abstract: Extracorporeal shock wave therapy may be an alternative treatment of calcifying tendinitis of the shoulder. Both treatment protocols gave equivalent results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 6 publications
(7 reference statements)
0
4
0
1
Order By: Relevance
“… 6 8.5 1200 + + + + + Plantar fasciopathy Hammer et al 110 + Piezoson 300 (Wolf) PE 0.20 (?) 3 7 3000 + + + + + 4 Calcifying tendonitis of the shoulder Seil et al 111 + Piezolith 2501 (Wolf) PE 0.10 and 0.30 (?) 3 7 5000 + + + + 1 5000 Loew et al 112 + MFL 5000 (Philips) and Compact (Dornier) EH 0.10 …”
Section: Resultsunclassified
“… 6 8.5 1200 + + + + + Plantar fasciopathy Hammer et al 110 + Piezoson 300 (Wolf) PE 0.20 (?) 3 7 3000 + + + + + 4 Calcifying tendonitis of the shoulder Seil et al 111 + Piezolith 2501 (Wolf) PE 0.10 and 0.30 (?) 3 7 5000 + + + + 1 5000 Loew et al 112 + MFL 5000 (Philips) and Compact (Dornier) EH 0.10 …”
Section: Resultsunclassified
“…Many authors have reported good results with low- or high-energy shock wave therapy in patients with calcifying tendinitis of the shoulder [2, 8, 25, 33, 39]. Rompe et al [30] compared ESWT with conventional surgery in the treatment of calcifying tendinitis of the shoulder.…”
Section: Discussionmentioning
confidence: 99%
“…A possible influence of failed preoperative ESWT on postoperative results after arthroscopic treatment of calcifying tendonitis was to our knowledge not investigated in the literature. But this becomes relevant as the success rates of ESWT in the treatment of calcifying tendonitis vary from 28 to 70% in the literature [17, 18, 26]. This implies that 30–70% require surgical treatment after ESWT.…”
Section: Discussionmentioning
confidence: 99%
“…But the influence of a failed preoperative ESWT on the clinical outcome after arthroscopic removal of the calcific deposit was to our knowledge not investigated in recent studies. However, a possible influence might be of great importance concerning the treatment regimen as the success rates of ESWT are reported from 28 to 70% [17, 18, 26] in the literature, which means that 30–70% of the patients might undergo surgery after failed ESWT.…”
Section: Introductionmentioning
confidence: 99%